Effect of magnetic field on corrosion behavior of Indian reduced activation ferritic/martensitic steel in liquid Pb–Li. (17th September 2019) - Chakraborty, P.; Singh, V.; Trivedi, P.; Malhotra, S.; Singh, K.; Mukherjee, P.; Kain, V.; Tewari, R.
Abstract: In the present study, the effect of a magnetic field on the corrosion of Indian reduced-activation ferritic/martensitic steel (IN RAFMS) in flowing lead–lithium eutectic (Pb–Li) has been studied in an electromagnetic-pump-driven loop (EMPPIL-M). The loop was operated for 2800 h at an average flow velocity of 1.5 m s −1 with a 0.5 T magnetic field over the IN RAFMS samples. The corrosion rate in the presence of a magnetic field at a temperature of 773 K was found to be 1.3 times higher than that observed in the absence of a magnetic field. Non-uniform corrosion, resulting in the formation of distinct surface features, was observed over the surface of the sample located inside the magnetic field. Pb–Li attack in the presence of a magnetic field was not only confined to the prior austenite and martensitic lath boundaries (as in the absence of magnetic field), but also occurred in the intra-lath regions resulting in the formation of substructures. The development of electric potential over metallic samples and significant gradients in Pb–Li flow due to the magnetohydrodynamic effect played a major role in the formation of surface features and accelerating the corrosion rate within the magnetic field. On the other hand, the increase in the depletion of iron from the steel matrix observed in the presence of the magnetic field was a result of its direct interaction with the field parameters.